2007
DOI: 10.1158/0008-5472.can-07-0107
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Blockade of the Human Eag1 Potassium Channel Function Exerts Antitumor Activity

Abstract: The potassium channel ether à go-go has been directly linked to cellular proliferation and transformation, although its physiologic role(s) are as of yet unknown. The specific blockade of human Eag1 (hEag1) may not only allow the dissection of the role of the channel in distinct physiologic processes, but because of the implication of hEag1 in tumor biology, it may also offer an opportunity for the treatment of cancer. However, members of the potassium channel superfamily are structurally very similar to one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
186
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(219 citation statements)
references
References 32 publications
(35 reference statements)
4
186
0
4
Order By: Relevance
“…Ether-á-go-go-1 (EAG1, KCNH1, K V 10.1) is a CNS-localized voltage-gated K þ channel that is found ectopically expressed in many solid tumours [25]. Monoclonal antibodies against human EAG1, developed by Stuhmer's and Pardo's groups, might represent a suitable tool in cancer therapy [26]. K V 10.1 expression might offer an advantage to tumours through increased vascularization and resistance to hypoxia: indeed, EAG1 regulates cellular oxygen homeostasis, increasing HIF-1 activity, and thereby VEGF secretion and tumour vascularization [27]; accordingly, EAG1 silencing inhibits tumour growth and angiogenesis in osteosarcoma in vivo [28] (table 1 and figure 2).…”
Section: Voltage-gated Channelsmentioning
confidence: 99%
“…Ether-á-go-go-1 (EAG1, KCNH1, K V 10.1) is a CNS-localized voltage-gated K þ channel that is found ectopically expressed in many solid tumours [25]. Monoclonal antibodies against human EAG1, developed by Stuhmer's and Pardo's groups, might represent a suitable tool in cancer therapy [26]. K V 10.1 expression might offer an advantage to tumours through increased vascularization and resistance to hypoxia: indeed, EAG1 regulates cellular oxygen homeostasis, increasing HIF-1 activity, and thereby VEGF secretion and tumour vascularization [27]; accordingly, EAG1 silencing inhibits tumour growth and angiogenesis in osteosarcoma in vivo [28] (table 1 and figure 2).…”
Section: Voltage-gated Channelsmentioning
confidence: 99%
“…Generating monoclonal antibodies has proven to be an effective strategy to perturb the function of cell surface proteins. As a proof of principle, it has been demonstrated that a highly specific extracellular epitope-targeting EAG1 monoclonal antibody exhibited antitumor activity in mouse (Gómez-Varela et al, 2007). Given the fact that EAG1 is highly expressed in 70% of human cancers but minimally present in non-CNS normal tissues, dye-tagged EAG1 antibody also possesses the potential for selective visualization of tumor cells for diagnostic purposes (Pardo et al, 2005).…”
Section: Potassium Channels In Cell Migration and Metastasismentioning
confidence: 99%
“…Moreover, cerebellum infusion caused cerebellar ataxia in mice, establishing a link between anti-voltage-gated calcium channel antibodies and pathogenesis [19] . Besides regulating neural excitability, some E3-targeted antibodies could modulate store-operated or agonist-evoked Ca 2+ entry [20][21][22][23][24][25] , oligodendrocyte proliferation and migration [26] , and tumor growth [27,28] . Channel regions that are not in the immediate vicinity of pore-forming region can be equally useful as active antibody targets.…”
Section: Development Of Active Antibodiesmentioning
confidence: 99%